Teknik Kontainerisasi dan Virtualisasi Sebagai Solusi Untuk Meningkatkan Portabilitas dan Skalabilitas Sistem Operasi Ubuntu - Rahman, Rakhmadi; Khalifah, Nur Ayu; Antoni, Wahyudi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research explores containerization and virtualization innovations as methods to increase the portability and scalability of the Ubuntu operating system. In an era of rapidly evolving technology, the ability to optimize resource use and simplify application distribution has become increasingly important. Containerization allows applications to run consistently across multiple environments by packaging all required dependencies. Meanwhile, virtualization allows multiple operating systems to run on a single physical piece of hardware, increasing efficiency and flexibility. This study examines the benefits, challenges, and implementation of these two techniques in the context of the Ubuntu operating system, offering in-depth insights and practical solutions that can be adopted by developers and system administrators. Thus, this research makes a significant contribution to the understanding and application of containerization and virtualization technologies to improve the performance and adaptability of operating systems in modern computing environments.